ANALYSIS OF STUDENTS MATHEMATICAL COMMUNICATION OF JUNIOR HIGH SCHOOL (SMP) THROUGH THE SAVI (SOMATIC, AUDITORY, VISUALIZATION, INTELLECTUALLY) APPROACH - Mazidah Maghfiroh; Baiduri Baiduri; Siti Khoiruli Ummah (Department of Mathematics Education University of Muhammadiyah Malang, 2017)
The purpose of this research is to analyze the students’ mathematicalcommunication in junior high school verbally as well as written by means theapproach of SAVI. This research uses qualitative approach with descriptiveresearch type. The subjects of this study totally 31 students of junior highschool on a class VIII, while the object is the students’ mathematicalcommunication, verbal as well as written using the approach of SAVI. Theinstrument used in this study are observation and test sheets. The data will beanalyzed using three plots, namely: data reduction, data presentations andsummarizing. The result of this study shows that students’ verbalcommunication in mathematics by means the approach of SAVI is in goodcategory. Students can finely declare the examples, explain mathematicsrepresentations, give questions and answers, declare the situation of aproblem in mathematical model, discuss a problem, conclude the result ofthe discussion and make summary related to the subject. The writtenmathematical communication of students is also in good category. Studentscan do well in writing mathematical ideas and representations, findingimportant points, rewriting the test in mathematical model, finishing theproblem and wraiting the summary related to the subject.